MODIS Observed Spatiotemporal Variation of Snow Cover in Zanskar Valley, North-Western Himalaya - Khali, Harish; Pandey, Pratima; Ali, Sheikh Nawaz; Champatiray, Prashant K. (Frontiers in Water, 2022)
The investigation of variations in the snow cover in response to the ongoing climate change is crucial for the understanding of hydrological and climatological processes in the Himalaya. Apart from contributing significantly to river discharge, the extent of the snow cover influences glacier nourishment, melting dynamics, and the intensity of the summer monsoon. Considering that the meteorological data is often scarce and unevenly distributed in the high mountain region, remote sensing studies become particularly crucial. In this study, we investigate the spatiotemporal characteristics and trends of snow cover percentage in Zanskar valley using the Moderate Resolution Imaging Spectroradiometer (MODIS) eight-day snow cover product (MOD10A2) from 2001 to 2021. Our findings indicate that the proportion of snow cover in the Zanskar valley has not decreased significantly during the last two decades. The annual average snow cover in Zanskar is 68%, with a maximum in the month of March (96%) and minimum in August (32%). Trend analysis showed no change in the snow cover below an altitude of 3500 m above mean sea level (asl) during the study period. The majority of the changes in snow cover percentage occurred between an altitude of ~4,500 and 5,500 m asl. An overall positive trend in the percentage of snow cover was observed from 2001 to 2021. The snow cover data was also compared to the Climatic Research Unit's (CRU) station interpolated data to look for any substantial contradiction; however any significant incongruity was not observed.